SISTEM PERKULIAHAN BERBASIS E-LEARNING PADA FAKULTAS TEKNOLOGI INFORMASI DAN KOMUNIKASI UNIVERSITAS SEMARANG - Henny Indriyawati; Didin Herlinudinkhaji; Soiful Hadi (Jurnal Transformatika, 2018)
The lecture system has been done in the Faculty of Information and Communication Technology (FTIK) was using of method meeting face-to-face. The lecturers were required to meet with students in accordance with the rules.The methods of lecture was conducted by lecturers by using books were making the students were being losted attractive. That causes students who were weak in memorization and difficult to remember the formulas and programming syntax provided by the lecturers resulting in students being lazy to learn and bored. Online lectures are one of the interactive learning facilities that allow lecturers and students to communicate without face to face directly using online media.Lecturers and students can communicated using internet media with software and support.Lecturers can provide important information to students by utilizing online lectures.This then makes the reason for utilizing information technology to implement an online e-learning based lecture system by applying the principles of flexibility, effectiveness, and efficiency